In order to solve the expression "a^5 - bc + 4a ÷ c" when a = 2, b = 3, and c is not given, we need to substitute the values of a, b, and c into the expression and then simplify it.
Substituting the values given, the expression becomes:
2^5 - 3c + 4(2) ÷ c
Simplifying further using the order of operations (BIDMAS/PEMDAS):
= 32 - 3c + 8 ÷ c
We cannot simplify it further without knowing the value of c.
a^5 − bc + 4a ÷ c when a = 2, b = 3, and c
3 answers
c = to 8
Great! Now that we know c is 8, let's substitute that value into the expression:
2^5 - 3(8) + 4(2) ÷ 8
Using the order of operations:
= 32 - 24 + 8 ÷ 8
= 32 - 24 + 1
= 9
So, when a = 2, b = 3, and c = 8, the expression "a^5 - bc + 4a ÷ c" equals 9.
2^5 - 3(8) + 4(2) ÷ 8
Using the order of operations:
= 32 - 24 + 8 ÷ 8
= 32 - 24 + 1
= 9
So, when a = 2, b = 3, and c = 8, the expression "a^5 - bc + 4a ÷ c" equals 9.